3D bioprinted tumor model with extracellular matrix enhanced bioinks for nanoparticle evaluation. (24th January 2022) - Chen, You; Xu, Langtao; Li, Weilin; Chen, Wanqi; He, Qiubei; Zhang, Xiaoge; Tang, Junjie; Wang, Yizhen; Liu, Bo; Liu, Jie
Abstract: The traditional evaluation of nanoparticles (NPs) is mainly based on 2D cell culture and animal models. However, these models are difficult to accurately represent human tumor microenvironment (TME) and fail to systematically study the complex transportation of NPs, thus limiting the translation of nano-drug formulations to clinical studies. This study reports a tumor model fabricated via 3D bioprinting with adipose decellularized extracellular matrix (ECM) enhanced hybrid bioink. Compared with 2D cultured cells, the 3D printed tumor models with multicellular spheroids formation are closer to real tumor in protein, gene expression and tumorigenicity both in vitro and in vivo . Two characteristics of TME, ECM remodeling and epithelial-mesenchymal transition, are tracked simultaneously under 3D conditions. Furthermore, the cellular uptake efficiency of two different NPs is significantly lower in the printed 3D tumor model than the 2D individual cells, and higher drug resistance is observed in 3D group, which suggest the ECM barrier of tumor can significantly affect the permeability of NPs. These results suggest that this 3D printed tumor model is capable of mimicking the multiple TME, potentially providing a more accurate platform for the design and development of NPs before moving into animal and clinical trials.